The Impact of Remuneration as Reward System on Job Satisfaction within the Hospitality Industries in Ghana - Adam, Abdul Kahar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This research used a qualitative study method which is to draw analysis from inductive angles. It has the following objectives as first to determine the impact of remuneration has on job satisfaction of employees, secondly, to further understand whether there is equity in remuneration policies that are applied to employees in general, and thirdly, to establish other remuneration systems that exists in most hospitality pay policies. The aim of this research is to assess the impact of remuneration and job satisfaction among hotel workers, there is the need to gather data on remuneration and job satisfaction of hospitality service in Ghana. This is an inductive study based on non-probability sampling technique. A quota sampling of 50 AH Hotel workers responded to the questionnaire. Quota sampling is a non-probability sampling method that relies on the non-random selection or convenience of a predetermined number or proportion of units. The research designed closed ended and open questions in the interview questionnaire (as data collection instrument in qualitative nature) which the respondents gave their feedback. The research findings shows that remuneration payment has greater impact on job satisfaction because many of the employees were happy with their salaries/wages. This is the more reason why they are retained as loyal staff with good morale behaviours, punctuality at work, and are also, good team players.